THE ROLE OF UNIVERSAL GRAMMAR AND AGE IN SECOND LANGUAGE ACQUISITION - Febria Zananda, Tiray (Enrich: Jurnal Pendidikan, Bahasa, Sastra dan Linguistik, 2022)
The term of Second Language Acquisition (SLA) is refers to the acquisition of second language in any stage of age, can be children or adults. In learning Second Language Acquisition, people can learn it because they have Universal Grammar (UG). UG is an “innate” for everyone.